Knowledge Management Diagnostics in Software Development Organizations: a Systematic Literature Review - Maciel, Claudia P.; de Souza, Érica Ferreira; Falbo, Ricardo de Almeida; Felizardo, Katia Romero; Vijaykumar, Nandamudi L. (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2018: Anais do XVII Simpósio Brasileiro de Qualidade de Software, 2018)
Context: Managing knowledge is one of the main challenges for software development organizations. Thus, the principles of Knowledge Management (KM) are presented as determinant and effective factors for the software product quality. There are several approaches to applying KM in an organization. However, for a KM approaches to succeed, it is important to conduct a KM diagnostic in order to analyze the KM current state that already exists in the organization. Objective: The objective of this paper is to present the results of a Systematic Literature Review (SLR) conducted to summarize existing research on KM diagnostic in software development organizations. Method: SLR was performed by searching four electronic databases. We also performed backward snowballing from reference lists of selected studies. Results: From the SLR, we identified 24 studies addressing investigated differents approaches related to KM diagnostics in software development organizations. Conclusion: Based on our results we conclude that in the software engineering context the KM diagnosis practice still does not seem consolidated.